Desain lansekap bantaran Tukad Badung sebagai ruang terbuka non hijau publik di Kota Denpasar - Handayana, Ketut Adikresna; Kohdrata, Naniek; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap; Vol.4, No.1, April 2018, 2018)
Design of Badung riverscape as non-green public open space in Denpasar City. Tukad Badung Riverscape in Pemogan Village is one of the riverscape in Denpasar City which has the potential to be designed as a Non-green Public Open Space (NPOS). NPOS is a place that can be used for the people to do their activities or recreation. This study aims to find out the potentials, problems and produce a design concept of Tukad Badung Riverscape in the Pemogan Village. The method used in this study was field survey with observation techniques, interviews, and literature study. Stages of this research are inventory, analysis, and synthesis which at the same time is the foundation in making design. The results indicated it had potentials and problems exist in Tukad Badung were people activities and Tukad Badung has wide riverbanks, meanwhile the problems were accessibility, plant, land, cleanliness, and facilities. The concept of design produced in this research was Balinese natural metaphor that takes the form of rice field terraces and beach waves. Suggestions that can be given are suggestions or recommendations for the government of Denpasar City such as NPOS design.